Particular Monuments and Archaeological Materials from The Dobrujan Cultural Heritage - Sorin Marcel COLESNIUC (Annals: Series on History and Archaeology (Academy of Romanian Scientists))
The archaeological research that we have made as site scientific manager or as member in various research collectives, in the ancient cities of Tomis, Callatis, Sacidava, Sucidava and in other archaeological sites in Constanța County, have had as a result the discovery of many monuments and archaeological materials, remarkably important for the history of the land between the Danube River and the Black Sea and for our national history. Some of these we have presented, in September 2023, at the National Scientific Fall Conference of the Academy of Romanian Scientists.[1]